Oral health status and treatment needs among patients with oral potentially malignant disorders - A cross-sectional study - Padma K Bhat; Nayana Mohandas; M Y Jayachandra; Vinod Rangan (Wolters Kluwer Medknow Publications, 2024)
Background: Oral potentially malignant disorders (OPMDs) such as oral leukoplakia, erythroplakia, lichen planus, and oral submucous fibrosis have been shown to have a high rate of transformation to oral cancer. Although many studies have already been done on the risk factors of OPMDs and oral cancer, there are only a few literature on oral health status of patients suffering from OPMDs in Indian scenario. Aim: The aim of this study was to assess the oral health status and treatment needs of patients with OPMDs. Methodology: A descriptive cross-sectional survey was carried out at the Department of Oncology, Rajarajeswhwari Medical college and hospital and Outpatient Department of Rajarajeswari Dental College and Hospital in Bengaluru after obtaining required permission from the concerned authorities and due ethical clearance. Clinical examination was conducted using the World Health Organization Oral Health Assessment Form for Adults, 2013. Results: Majority of the participants were males, with an age range of 21-75 years, and majority were suffering from leukoplakia (49.9%). Decayed, missing, and filled tooth component was statistically significant (P < 0.05) when comparing mean Decayed, Missing, and Filled Teeth scores between age, gender, and socioeconomic status. The highest CPI score (score of 2) was found highest in participants (32.47%) with leukoplakia. Regarding the treatment needs, about 94.5% of the participants needed prompt treatment (including scaling). Conclusion: Results revealed that the oral health status of participants with OPMD was average. The CPI score (periodontal status) was high in most participants with OPMD, with the maximum score of 2 found in a large number of participants.